(untitled) (Edad Media. Revista de Historia, 2023)
The aim of this paper is to analyse the participation of the Franciscan female convents in some aspects of the economy of the cities in which they were erected. We focus on the two main cities of the kingdom of Seville, the capital and Jerez de La Frontera, from 1410 until 1520. The documentation on which this study is based originates from the diplomatic collections of the convents and the collections of notarial protocols of both cities. Thus, we will be able to demonstrate the nuns’ ability to manage their estate and to show the wide range of links they were able to forge with their fellow citizens.